Answer:
(x, y, z) → (18, 22, 9)
Explanation:
sum of three numbers is 49
x + y + z = 49
second number is 5 less than three times the third number
y = 3z - 5
first number is twice amount of third number
x = 2z
set of equations
x + y + z = 49
y = 3z - 5
x = 2z
plug in 2nd and 3rd equation into first
(2z) + (3z - 5) + z = 49
combine like terms
2z + 3z - 5 + z = 49
6z - 5 = 49
add 5 to both sides
6z = 54
divide by 6
z = 9
plug z into 2nd and 3rd equations
y = 3(9) - 5
y = 27 - 5
y = 22
x = 2(9)
x = 18
check:
18 + 22 + 9 = 49
(x, y, z) → (18, 22, 9)